Modification of solution processed thin chalcogenide films composition by source solution doping - Pálka, Karel; Šlang, Stanislav; Jančálek, Jiří; Vlček, Miroslav (Elsevier Science BV, 2019)
Solution processed thin chalcogenide films have attracted noteworthy attention due to the simplicity and thus low cost of applicable deposition techniques (e.g. spin-coating). In presented work we demonstrate the possibility to modify the thin films composition by altering the composition of source glass solution, which significantly improves tailoring potential of solution based thin films. Thin films of As30S70 composition of specular optical quality were prepared from As40S60 bulk glass and pure elemental sulfur by spin-coating method. The As40S60 source bulk glass is also commercially available as AMTIR-6. Optical properties, thickness, chemical resistance, structure and elemental composition of the thin films were studied in dependence on the annealing temperature. Results were compared with properties of thin films of the same As30S70 composition prepared by standard procedure from As30S70 bulk glass. Different thermo-induced structural transformations were observed in both sets of samples resulting in As30S70 thin films of very similar properties after thermal stabilization at 120 °C.
Modifikace z roztoku připravených chalkogenidových tenkých vrstev pomocí dopace zásobního roztoku
Keywords: Chalcogenide glass; Spin-coating; Thin films; Solution doping; Chalkogenidová skla; Spin-coating; Tenké vrstvy; Dopace roztoků